SME Performance Analysis: Reviewed from the TOE Framework Perspective to Support Sustainable Economic Resilience in Indonesia - Uray, Andrey Indra Maulana; Setiawan, Aris; Araftake Blikololong, Yohanes Gala (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
Adopting e-commerce in the business sector requires technological resources such as IT infrastructure, internet connectivity, software and hardware systems, as well as qualified IT personnel which often poses financial challenges for small and medium-sized enterprises (SMEs). This study investigates whether technology adoption by SMEs translates into competitive advantage and improved performance. The research emphasizes the Technology–Organization–Environment (TOE) framework, which highlights the role of technological readiness, organizational capacity, and environmental factors in shaping competitiveness. Combined with the diffusion of innovation theory, this framework is expected to guide SMEs in developing effective strategies for technology adoption. A quantitative approach was applied using survey methods and data analysis through Partial Least Squares Structural Equation Modeling (PLS-SEM). Purposive sampling yielded 398 SME respondents across Indonesia. Findings show that entrepreneurial orientation and technological readiness significantly influence SME performance—measured by personal wealth and firm growth—through competitive advantage. Entrepreneurial orientation exhibits a full mediation effect, while technological readiness demonstrates partial mediation. These results suggest that within the TOE framework, technology, organization, and environment must first generate competitive advantage before exerting a significant impact on SME performance. This study confirms that integrating TOE with diffusion of innovation theory provides a strategic foundation for SMEs to adopt technology effectively, enhance competitiveness, and achieve sustainable growth.